Effect of Lanthanum Substitution on the Structure and Conductivity of LNMC Samples as Battery Cathodes: Maya Puspitasari Izaak, Y. E. Gunanto, H. Sitompul, Y. Purwamargapratala - Maya Puspitasari Izaak Maya Puspitasari Izaak; Y. E. Gunanto Y. E. Gunanto; H. Sitompul H. Sitompul; Y. Purwamargapratala Y. Purwamargapratala (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
Lithium-Nickel-Manganese-Cobalt (LNMC) is one of the most successful types of lithium-ion batteries in the market. This battery is a combination of three main metals, nickel, manganese, and cobalt, with relatively the same composition. Measurements was performed on three LMNC materials combined with La composites to reduce the toxicity level of the Cobalt. The purpose of this research is to synthesize and characterize LMNC materials with certain La combinations, thus it is expected to be able to be used as battery cathode. Characterization of materials was carried out using XRD, SEM, and LCR-meter. In this study, we succeed in synthesizing and characterizing LMNC materials with a size of about 150-750 nm. The LCR-meter characterization found conductivity values of approximately 1.06×10-3, 7.07×1010-4, and 4.05×1010-3 S/cm at 100 Hz, 2.29×1010-3, 2.56×1010-3, and 1.34×1010-2 S/cm at 2.5 MHz, 2.74×1010-3, 3.04×1010-3, and 1.51×1010-2 S/cm at 5 MHz for La dopping with x = 0.01, 0.03, and 0.05, respectively. The La substitution increases the conductivity value and reduces the particle size to nanoscale.